Mister Rogers' neighborhood : a visual history - Lybarger, Tim; Wagner, Melissa; McGuiggan, Jenna; Hanks, Tom; Fred Rogers Productions (PITTSBURGH, Pennsylvania) (New York : Clarkson Potter/Publishers, 2019)
"Go behind the scenes of Mister Rogers' Neighborhood with this unprecedented dive into its storied history. Featuring exclusive photographs; a guide to the characters, puppets, and episodes; original interviews with Yo-Yo Ma, Winton Marsalis, and cast and crew; and rare ephemera, this extraordinary book reveals the inner workings of the show, making it the ultimate fan guide just in time for It's a Beautiful Day in the Neighborhood, the film starring Tom Hanks"--